Female Masculinity of Alanna Trebond in Tamora Pierce’s Alanna: The First Adventure (Song of the Lioness) - SITI WULANDARI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
Masculinity studies have focused almost exclusively on masculinity performed by men. However this study focuses on masculinity produced by Alanna Trebond as the main female character in Alanna: The First Adventure (Song of the Lioness) novel by Tamora Pierce. The first problem discussed is how masculinity described by Alanna as the main female character in the novel and the second problem concern in what factors that leads in her masculinity. This literary study falls under the umbrella of gender studies, deploys Peter Lehman’s concept of Masculinity and theory of female masculinity by Judith Halberstam to bring out the representation of female masculinity in the novel. Based on the analysis, this study shows that Alanna Trebond has more masculine character than feminine in the form of Courageous, Heroism and Leadership skill. This masculine characteristic is formed and caused by several factors, namely family upbringing and social environment. Keywords: female masculinity, gender, family upbringing Studi maskulinitas telah berfokus hampir secara eksklusif pada maskulinitas yang dilakukan oleh pria. Namun studi ini berfokus pada kejantanan yang diproduksi oleh Alanna Trebond sebagai karakter wanita utama dalam novel Alanna: The First Adventure (Song of the Lioness) oleh Tamora Pierce. Masalah pertama yang dibahas adalah bagaimana maskulinitas digambarkan oleh Alanna sebagai karakter utama wanita dalam novel dan masalah kedua menyangkut faktor apa yang menyebabkan maskulinitasnya. Studi sastra ini berada di bawah payung studi gender, menggunakan konsep Maskulinitas karya Peter Lehman dan teori maskulinitas wanita dari Judith Halberstam untuk menampilkan representasi maskulinitas wanita dalam novel tersebut. Berdasarkan analisis, penelitian ini menunjukkan bahwa Alanna Trebond memiliki karakter lebih maskulin daripada feminin dalam bentuk keberanian, kepahlawanan dan keterampilan kepemimpinan. Karakteristik maskulin ini terbentuk dan disebabkan oleh beberapa faktor, yaitu pengasuhan keluarga dan lingkungan sosial. Kata kunci: perempuan maskulin, jenis kelamin, pengasuhan keluarga